Legal Implications of Islamic Banking in Advancing Sustainable Finance for Indonesia’s Net-Zero-Emission Programme - Septyanun, Nurjannah; Shalihah, Fithriatus; Absori; Wahyudi, Ikhsan; Masum, Ahmad (Faculty of Law, Jambi University, 2025)
Islamic banking is increasingly expected to contribute to Indonesia’s net-zero-emission agenda, yet the integration between Shariah principles and environmental governance remains limited. Although national development plans recognise Islamic finance as an enabler of green transformation, no coherent framework currently links maqashid al-Shariah, mashalah, and ecological sustainability with forest governance and carbon-economic-value mechanisms. This study aims to fill the gap by examining the potential of Islamic banking instruments to support low-carbon development, particularly in West Nusa Tenggara, a pioneer region for carbon-value implementation. Employing a mixed doctrinal–empirical method—including legislative review, conceptual analysis, observation, and a questionnaire distributed—the study identifies structural weaknesses in existing financing systems, such as collateral dependence, regulatory fragmentation, and ecological risk. While the empirical findings reveal strong societal support for Shariah-compliant green financing, the Islamic banking instruments such as mudarabah, musyarakah, istisna, green sukuk, and cash-waqf-linked sukuk provide equitable risk-sharing, asset-based long-term financing, and supportive social-finance mechanisms. The study concludes that Islamic banking can meaningfully contribute to Indonesia’s net-zero targets, provided that regulatory harmonisation, operational guidelines, and government incentives are strengthened to institutionalise Shariah-compliant green finance.